2010
DOI: 10.1901/jeab.2010.94-315
|View full text |Cite
|
Sign up to set email alerts
|

Choice in Quail Neonates: The Origins of Generalized Matching

Abstract: Although newborns have surprised scientists with their learning skills, proficiency on concurrent schedules of reinforcement requires (in effect) the ability to integrate and compare behaviorconsequence relations over time. Can very young animals obey the quantitative relation that applies to such repeated choices, the generalized matching law? The provenance of the skill is not well understood, and this study provides the first investigation of matching in neonates. Northern bobwhite (Colinus virginianus) hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When the behaviors of nonhumans and humans are studied in similar choice situations, similar behavior patterns are frequently found. For instance, numerous studies on choice with concurrent variable interval schedules have found that the response proportions of both nonhumans (e.g., Herrnstein, 1961; Schneider & Lickliter, 2010) and humans (e.g., Ecott & Critchfield, 2004; McDowell & Caron, 2010) tend to approximate the reinforcement proportions, such that their response distributions can be described by the generalized matching law (Baum, 1979; Davison & McCarthy, 1988). In choices between immediate and delayed reinforcers, both nonhumans (e.g., Mazur & Biondi, 2009; Woolverton, Myerson, & Green, 2007) and humans (e.g., Green, Fry, & Myerson, 1994) display patterns of delay discounting that are well described by a hyperbolic equation (see Madden & Bickel, 2010; Odum, 2011).…”
mentioning
confidence: 99%
“…When the behaviors of nonhumans and humans are studied in similar choice situations, similar behavior patterns are frequently found. For instance, numerous studies on choice with concurrent variable interval schedules have found that the response proportions of both nonhumans (e.g., Herrnstein, 1961; Schneider & Lickliter, 2010) and humans (e.g., Ecott & Critchfield, 2004; McDowell & Caron, 2010) tend to approximate the reinforcement proportions, such that their response distributions can be described by the generalized matching law (Baum, 1979; Davison & McCarthy, 1988). In choices between immediate and delayed reinforcers, both nonhumans (e.g., Mazur & Biondi, 2009; Woolverton, Myerson, & Green, 2007) and humans (e.g., Green, Fry, & Myerson, 1994) display patterns of delay discounting that are well described by a hyperbolic equation (see Madden & Bickel, 2010; Odum, 2011).…”
mentioning
confidence: 99%
“…Trained animals, with considerable previous experience in the different reinforcement rates of the options, are quick to adapt to unpredictable changes in relative reinforcement rates [ 7 - 17 ]. However, few attempts have been made to explore the patterns of acquisition of matching behavior in experimentally naïve animals [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%